2017
DOI: 10.3164/jcbn.16-60
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature plasma equipment applied on surgical hemostasis and wound healings

Abstract: Low temperature plasma (LTP) coagulation equipment, which avoids causing burn injuries to patients, has been introducing into minimally invasive surgery. The mechanism by which this equipment stops bleeding is to directly occupy the injury with the formed blood clots, and different from the mechanism of the common electrical hemostatic devices that cauterize the tissues around the bleeding to stem the blood flow. A noteworthy point is that LTP treatment with our equipment is not confined only to the blood coag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 32 publications
0
57
1
Order By: Relevance
“…Great efforts are currently made extending the range of plasma applications with different devices. This includes blood coagulation [Amritkar et al, 2013;Aleinik et al, 2017;Miyamoto et al, 2017], ophthalmology [Rosani et al, 2015;Ye et al, 2015;Recek et al, 2016], oncology [Ye et al, 2015;Mirpour et al, 2016;Binenbaum et al, 2017], and various diseases in dermatology [Daeschlein et al, 2010[Daeschlein et al, , 2011Klebes et al, 2014]. Addressing not only the efficacy but also safety of different plasma sources or their optimum operational settings, genotoxic testing is indispensable.…”
Section: Introductionmentioning
confidence: 99%
“…Great efforts are currently made extending the range of plasma applications with different devices. This includes blood coagulation [Amritkar et al, 2013;Aleinik et al, 2017;Miyamoto et al, 2017], ophthalmology [Rosani et al, 2015;Ye et al, 2015;Recek et al, 2016], oncology [Ye et al, 2015;Mirpour et al, 2016;Binenbaum et al, 2017], and various diseases in dermatology [Daeschlein et al, 2010[Daeschlein et al, , 2011Klebes et al, 2014]. Addressing not only the efficacy but also safety of different plasma sources or their optimum operational settings, genotoxic testing is indispensable.…”
Section: Introductionmentioning
confidence: 99%
“…(1) CAP can be applied to biological samples because it is produced at room temperature and normal atmospheric pressure. (2) Therefore, CAP has potential for biomedical applications such as wound healing, (3)(4)(5)(6) infection control, (7)(8)(9)(10) and cancer therapy. (11)(12)(13)(14) There are at least three types of CAP used for biological samples: 1) plasma jets, 2) corona discharge plasma sources, and 3) dielectric barrier discharge plasma sources.…”
mentioning
confidence: 99%
“…18 This mechanism is similar to the mechanism of surgical hemostats that stimulate aggregation of platelets and coagulation factors. 19 In a study by Pedroso et al, 20 this specific device was applied on porcine liver, kidney, and muscle tissue at different power levels and gas flows. It was shown that J-Plasma has minimal lateral and depth spread when it is applied to various tissue types, even at higher power settings or gas flow rates.…”
Section: Discussionmentioning
confidence: 99%